2017
DOI: 10.1155/2017/2465158
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Rational Haar Wavelet and Block Pulse Functions Method for Solving Population Growth Model and Abel Integral Equations

Abstract: We use a computational method based on rational Haar wavelet for solving nonlinear fractional integro-differential equations. To this end, we apply the operational matrix of fractional integration for rational Haar wavelet. Also, to show the efficiency of the proposed method, we solve particularly population growth model and Abel integral equations and compare the numerical results with the exact solutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…From Table 2, we infer that as the values of α increases, the attain solution of the proposed model increases and converge to the exact value zmax at α=1. Also, from Table 2, we found that our outcomes are sensibly better when contrasted with the outcomes acquired by 13,44 . The numerical outcomes propose that the nature of similar species population in a closed system relies upon the estimations of both α and κ .…”
Section: Numerical Results and Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…From Table 2, we infer that as the values of α increases, the attain solution of the proposed model increases and converge to the exact value zmax at α=1. Also, from Table 2, we found that our outcomes are sensibly better when contrasted with the outcomes acquired by 13,44 . The numerical outcomes propose that the nature of similar species population in a closed system relies upon the estimations of both α and κ .…”
Section: Numerical Results and Discussionmentioning
confidence: 56%
“…Also, from Table 2, we found that our outcomes are sensibly better when contrasted with the outcomes acquired by. 13,44 The numerical outcomes propose that the nature of similar species population in a closed system relies upon the estimations of both 𝛼 and 𝜅. Finally, in Figure 8, we present the three-dimensional graphs of our approximate solution for distinct values of 𝜅.…”
Section: Example 2 Consider the Following Nonlinear Logistic Equationmentioning
confidence: 95%
“…In this study, the polarity is identified by injecting pulse voltage into the hypothesized 􏽢 d axis. IPMSM transforms voltage and current components in the stationary coordinate system in accordance with Euler's theorem to yield the resultant vector equation [18][19][20][21][22][23][24][25], which is expressed as…”
Section: Polarity Identification By Pulse Voltage Injection Methodmentioning
confidence: 99%
“…These equations occur in different fields of the sciences. The solution methods of the Abel integral equations are collocation methods [9][10][11][12][13], Adomian decomposition methods [14][15][16], homotopy perturbation methods [17], quadrature methods [18][19][20], homotopy analysis methods [21], and Laplace transform methods [22][23][24][25][26]. Besides, Abel integral equations are also solved by using Chebyshev [27][28][29], Legendre [30,31], Taylor [32], Bernstein [33,34], Block-Pulse [35], and Laguerre [36] functions.…”
Section: Introductionmentioning
confidence: 99%